Pengaruh disiplin kerja dan komitmen organisasi terhadap kinerja pegawai pada kantor Dinas Pemberdayaan Masyarakat dan Pemerintahan Dusun Kabupaten Muara Bungo - Hidayat, Berryansyah; Amin, Shofia; Rosita, Sry (Jurnal Dinamika Manajemen, 2021)
Organizational commitment on employee performance at the Office of Community Empowerment and the Dusun Government of Muara Bungo Regency. The approach used in this research is a quantitative approach with associative analysis. The sampling technique used was saturated sampling. The number of samples taken in this study was all employees totaling 34 respondents. The results showed that the work discipline variable had a negative and insignificant effect on performance, and the organizational commitment variable showed a positive and significant impact on performance. The study results indicate that the variables of work discipline and organizational commitment together affect the performance of employees at the Office of Community Empowerment and the Dusun Government of Muara Bungo Regency.